The Indian chief as tragic hero : native resistance and the literatures of America, from Moctezuma to Tecumseh - Sayre, Gordon M. (Gordon Mitchell), 1964- (University of North Carolina Press, 2005)
Includes chapters on seven major resistance struggles, including the Pueblo Revolt of 1680 and the Natchez Massacre of 1729. This book offers an analysis of not only the tragedies and epics written about these leaders, but also their own speeches and strategies, as recorded in archival sources and narratives by adversaries.